Management of sigmoid volvulus: is early surgery justifiable?. (24th August 2012) - Yassaie, Omid; Thompson‐Fawcett, Mark; Rossaak, Jeremy
Abstract: Introduction: Sigmoid volvulus typically occurs in older patients who have multiple co‐morbidities. Therefore, often, a conservative approach to management is chosen. However, there is little data on long‐term outcomes of this approach in Australasia. The aim of this study was to review the recurrence and mortality outcomes of patients admitted to Dunedin Hospital with sigmoid volvulus. Methods: All cases of sigmoid volvulus admitted to the Department of General Surgery at Dunedin Hospital from January 1989 to January 2009 were identified using a prospective database, the Otago Clinical Audit. Mortality data was accessed from the National Births and Deaths Registry. Results: Fifty‐seven patients, median age of 68, were included in the study with 84 admissions for sigmoid volvulus. A total of 39 of the 57 patients ultimately had surgery, 26 on the index admission. Thirty‐one patients (61%) treated conservatively at index admission had a recurrence at a median of 31 days. Forty‐two per cent of the patients treated conservatively a second time suffered a further recurrence at a median of 144 days. There was no recurrence in patients who had surgery. There was no in‐hospital mortality reported in either group. There was one anastomotic leak in the surgical group. Minor complications included ileus, respiratory infections, urinary tract infection and a hernia. Conclusion: Early elective operation for cases of sigmoid volvulus is encouraged in patients without prohibitive co‐morbidities as this study shows a high recurrence rate in conservatively managed patients and a low morbidity and mortality in surgically managed patients.